The Development of Local History Learning Model Based on Progressivism to Promote Historical Thinking Skills - Asyrul Fikri; Mahdum Mahdum; Isjoni Isjoni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The issue is that history is generally taught in schools in a conventional manner, relying solely on textbook explanations and attempting to gather facts about what happened in the past. As a result, history classes have always come to be associated with memorization and recollection of past events, making it harder for students to acquire higher-order thinking abilities like historical thinking. To distribute the potential that students must possess, relevant paradigms, methods, tactics, models, and processes must be used to develop historical thinking abilities. The goal of this research is to develop a local history learning model based on the progressivism paradigm that will aid students in improving their historical thinking abilities. This study is a development studies project based on Thiagarajan, Semmel, and Semmel's 4D development design. The research stage is modified according to the needs and goals of the study. Interviews, open questionnaires, validation sheets, and historical thinking skills tests were used to gather data for the study. This study enlisted the participation of 160 students from Riau University's history education program. Our study's findings show that the local history learning model based on the progressive paradigm was valid and reliable as a learning model in local history learning and had a significant impact on students at Riau University's think historically. The summative evaluation indicated that the progressivism-based local history learning model was extremely effective in improving higher-order thinking abilities like historical thinking. Therefore, educators, including lecturers and teachers, may utilize this progressive